Tubular TiC fibre nanostructures as supercapacitor electrode materials with stable cycling life and wide-temperature performance - Xia, Xinhui (2015)
Highly active electrode materials with judicious design of nanostructure are important for the construction of high-performance electrochemical energy storage devices. In this work, we have fabricated a tubular TiC fibre cloth as an interesting type of stable supercapacitive material. Hollow microfibres of TiC are synthesized by carbothermal treatment of commercial T-shirt cotton fibres. To demonstrate the rationale of nanostructuring in energy storage, the hollow fibres are further covered by interwoven TiC nanotube branches, forming 3D tubular all-TiC hierarchical fibres with high electrical conductivity, high surface area, and high porosity. For energy storage functions, organic symmetric supercapacitors based on the hollow fibre–nanotube (HFNT) TiC cloth electrodes are assembled and thoroughly characterized. The TiC-based electrodes show very stable capacitance in long charge–discharge cycles and at different temperatures. In particular, the integrated TiC HFNT cloth electrodes show a reasonably high capacitance (185 F g−1 at 2 A g−1), better cycling stability at high-rates (e.g., 97% retention at room temperature after 150 000 cycles, and 67% at −15 °C after 50 000 cycles) than other control electrodes (e.g., pure carbon fibre cloths). It is envisaged that this 3D tubular TiC fibre cloth is also useful for solar cells and electrocatalysis.